Cardiac conditions in pregnancy and the role of midwives: A discussion paper. Issue 3 (1st April 2019) - Millington, Sandra; Magarey, Judith; Dekker, Gustaaf A.; Clark, Robyn A.
Abstract: Aim: This paper provides an overview of the two broad categories of cardiac conditions observed in pregnancy (congenital and acquired). It also identifies the midwives' role in the childbirth continuum and includes assessment, track and trigger systems and management during labour and delivery. Design: Discussion paper. Methods: Data were collected by reviewing international evidence and by searching computerized databases. Results: Research has identified that women with associated risk factors of a cardiac condition who delay pregnancy have an increased risk of experiencing cardiovascular complications in pregnancy with poorer outcomes. The Three Ps in a Pod clinical initiative in the United Kingdom highlights working as a team in multidisciplinary programmes to improve mothers' care and save lives. Midwives play a key role during pregnancy and need to be appraised in relation to cardiovascular disease observed in pregnancy, its potential risks and anticipated problems and within the continuum of care.